IoT networks for monitoring and detection of leakage in pipelines. (28th April 2022) - Bakhder, Seham S.; Aldabbagh, Ghadah; Dimitriou, Nikos; Alkhuraiji, Samar; Fadel, Mai; Bakhsh, Helen
Pipelines have been an important means of oil transport in recent years, especially in Saudi Arabia. Since oil pipelines have extensive length, tracking them is a critical task. Therefore, monitoring pipeline leaks has become a significant field of intelligent sensing systems. There are many challenges when monitoring long-distance pipelines, requiring energy efficiency. Wireless sensor networks (WSNs) deployed in oil pipelines provides solutions to address these challenges, but various issues must be considered, such as costs, scalability, and delay issues for monitoring systems. The recent advances in internet of things (IoTs) and the new LPWAN capabilities have promising benefits over monitoring systems. This paper investigates WSN systems in oil pipelines with IoT technologies. Also, it presents a LoRa as an LPWAN single-hop model for monitoring aboveground oil pipelines. The LoRa model is evaluated by using two scenarios and analysing the scalability and capacity of the LoRa and discussing the result.